POTENCY AND ACTIVITY OF SECONDARY METABOLITE OF Trichoderma harzianum AC1(b) J2 INHIBITOR GROWTH Colletotrichum capsici IPBCC 13.1098 - Nurkayah, Nurkayah; Nurnawati, Elisa; Widjajanti, Hary (BIOVALENTIA: Biological Research Journal, 2019)
Trichoderma harzianum is a fungus that can produce secondary metabolites which able to inhibit the growth of Colletotrichum capsici. a pathogenic fungus causing anthracnose in plants. the Aims of this research were to obtain and analyze the ability of secondary metabolites of Trichoderma harzianum AC1 (b) J2 isolated from Scleria poaeformis. to inhibit the growth of Colletotrichum capsici IPBCC13.1098. The secondary metabolite eluat of Trichoderma harzianum were tested for the antifungal activity toward Colletotrichum capsici IPBCC 13.1098. Fractionation was carried out by Column Chromatography and produced 31 eluat. The secondary metabolite eluat of Trichoderma harzianum with the highest inhibition zone diameter was eluat 1 with 8.4 mm in diameter. The secondary metabolite eluat with the highest value of inhibition zone was carried out by MIC test and thin layer chromatography (TLC). Based on the MIC results, the minimum inhibitory concentration of the secondary metabolite of Trichoderma harzianum to fungus Colletotrichum capsici was 250 ppm with inhibition zone diameter was 0.10 mm. The results of TLC showed orange spots on the TLC plate that indicated alkaloite compounds.